ANALISIS KINERJA KEUANGAN PADA PT BANK SYARIAH INDONESIA - Umiyati, Umiyati; Muthahari, Alif; Indayatun, Ratna (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
The analysis of financial performance plays a critical role in determining the success and sustainability of a financial institution, including Bank Syariah Indonesia. As a financial institution operating based on Islamic principles, Bank Syariah Indonesia faces unique challenges, both in terms of compliance with Islamic law and competition with conventional banks. The objective of this study is to examine the financial performance of PT Bank Syariah Indonesia (BSI) for the 2021–2023 period. The research employs a quantitative descriptive method. All indicators show positive trends, with an increase in ROA (Return on Assets) and a decrease in BOPO (Operational Costs to Operational Revenue), reflecting good efficiency and profitability. ROA and BOPO fall within the "Very Healthy" category, while ROE (Return on Equity) is in the "Healthy" category, indicating potential for more strategic equity management. BSI's financial performance is classified as healthy to very healthy. The consistently increasing FDR (Financing to Deposit Ratio) indicates aggressiveness in financing distribution. In 2021, FDR was in the "Very Healthy" category but declined to "Healthy" in 2022 and 2023. Nevertheless, FDR approaches the upper optimal limit (around 85%), necessitating caution to avoid liquidity pressures. BSI's CAR (Capital Adequacy Ratio) has consistently remained in the "Very Healthy" category for three consecutive years, far above Bank Indonesia's minimum threshold of 8%. A stable CAR ratio exceeding 20% reflects BSI's ability to manage risks and growth efficiently, providing a strong foundation for expanding financing or assets without compromising capital stability